2005
DOI: 10.1258/1355819054338997
|View full text |Cite
|
Sign up to set email alerts
|

Access to health care for people with learning disabilities in the UK: mapping the issues and reviewing the evidence

Abstract: There are important gaps in the knowledge base on access to health care for this group. While these need to be addressed, developing strategies to overcome identified barriers should be a priority, along with fuller evaluation of existing innovations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
144
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(157 citation statements)
references
References 34 publications
2
144
0
5
Order By: Relevance
“…Studies from the United States have described that using a computer interface as part of the registration process is efficient and feasible. 32,41 Participants in other studies have also reported broad support for collecting sociodemographic data, with some reservations if it is unclear why the data are being collected. 28,29,42 Similar to our study, others have found that race and ethnicity questions can be controversial, something that can be ameliorated by allowing patients to selfidentify in their own terms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from the United States have described that using a computer interface as part of the registration process is efficient and feasible. 32,41 Participants in other studies have also reported broad support for collecting sociodemographic data, with some reservations if it is unclear why the data are being collected. 28,29,42 Similar to our study, others have found that race and ethnicity questions can be controversial, something that can be ameliorated by allowing patients to selfidentify in their own terms.…”
Section: Discussionmentioning
confidence: 99%
“…4 Severity levels for ID are typically categorised by broad intelligence quotient (IQ), alongside the required deficits in independent living skills, into mild (IQ [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69], moderate (IQ [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], severe and profound (IQ < 20) ID. 5 Acknowledging the wide variation that exists between individuals with ID, typical abilities suggested for each category are outlined in Table 1 [based on World Health Organization (WHO) International Classification of Diseases, Tenth Edition (ICD-10)].…”
Section: Definition Of Intellectual Disability and Case Identificationmentioning
confidence: 99%
“…[63][64][65][66] Despite their increased health needs, they often find it difficult to access primary care services and to participate in health promotion activities. [67][68][69] Given the health inequalities among people with ID, and the possible increased risk of developing diabetes, people with ID have the potential to benefit from lifestyle changes (with appropriate support) that are addressed in lifestyle education programmes. However, the evidence base for diabetes prevention relates to the general adult population; literature focusing on ID is scarce.…”
Section: Diabetes Prevention In Adults With Intellectual Disabilitiesmentioning
confidence: 99%
“…Literature reviews and empirical studies that have examined reasons for non-participation in cervical screening programmes by women with intellectual disabilities have identified a number of specific barriers, including communication difficulties; perceived difficulties obtaining consent; attitudes of carers and staff; lack of accessible information; physical difficulties; limited liaison with specialist teams; and assumptions made by healthcare professionals (Stein and Allen, 1999;Broughton and Thomson, 2000;Broughton, 2002;Alborz et al, 2005;Wood and Douglas, 2007;Watts, 2008;Gribben and Bell, 2010).…”
Section: Introductionmentioning
confidence: 99%